Isaiah Berlin and the politics of freedom : "Two concepts of liberty" 50 years later - Baum, Bruce David, 1960-; Nichols, Robert, 1979- (New York : Routledge, 2013)
"Since his death in 1997, Isaiah Berlin's writings have generated continual interest among scholars and educated readers, especially in regard to his ideas about liberalism, value pluralism, and "positive" and "negative" liberty. Most books on Berlin have examined his general political theory, but this volume uses a contemporary perspective to focus specifically on his ideas about freedom and liberty. Isaiah Berlin and the Politics of Freedom brings together an integrated collection of essays by noted and emerging political theorists that commemorate in a critical spirit the recent 50th anniversary of Isaiah Berlin's famous lecture and essay, "Two Concepts of Liberty." The contributors use Berlin's essay as an occasion to rethink the larger politics of freedom from a twenty-first century standpoint, bringing Berlin's ideas into conversation with current political problems and perspectives rooted in postcolonial theory, feminist theory, democratic theory, and critical social theory. The editors begin by surveying the influence of Berlin's essay and the range of debates about freedom that it has inspired. Contributors' chapters then offer various analyses such as competing ways to contextualize Berlin's essay, how to reconsider Berlin's ideas in light of struggles over national self-determination, European colonialism, and racism, and how to view Berlin's controversial distinction between so-called "negative liberty" and "positive liberty." By relating Berlin's thinking about freedom to competing contemporary views of the politics of freedom, this book will be significant for both scholars of Berlin as well as people who are interested in larger debates about the meaning and conditions of freedom"--
pt. I. Berlin in context -- pt. II. Rethinking "Positive" and "Negative" freedom -- pt. III. Democratic pluralism and national self-determination -- pt. IV. Berlin and critical theories of freedom.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Berlin, Isaiah, -- 1909-1997.; Berlin, Isaiah, -- 1909-1997.; Liberty; Liberalism; Electronic books